An in silico approach for evaluation of rbcL and matK loci for DNA barcoding of Cucurbitaceae family - Viet The Ho; MINH PHUONG NGUYEN (Society for Indonesian Biodiversity, 2020)
Abstract. Ho VT, Nguyen MP. 2020. An in silico approach for evaluation of rbcL and matK loci for DNA barcoding of Cucurbitaceae family. Biodiversitas 21: 3879-3885. DNA barcodes have been used intensively to discriminate different species in Cucurbitaceae family. The main of this study is to evaluate the effectiveness of rbcL and matK loci for 16 species of Cucurbitaceae family by using in silico approach. For analysis, sequences were firstly retrieved from NCBI and then calculated for sequence parameters. Sequences were then aligned and constructed phylogenetic try and examined for species resolution ability. The obtained data show the variability of resolving capacity among species. rbcL region is suitable for distinguishing five species namely S. edule, M. cochinchinensis, L. aegyptiaca, C. melo, and C. pepo, whereas matK locus is more proper for different five species consisting of M. balsamina, M. cochinchinensis, M. charantia, S. edule, and C. sativus. The resolving power is improved sharply by analyzing the rbcL + matK combination with up to nine species consisting of C. lanatus, B. hispida, C. melo, C. sativus, C. pepo, C. agryrosperma, L. aegyptiaca, S. edule, and M. cochinchinensis. Therefore, the integration of rbcL and matK loci may improve the competence of assessing genetic relatedness at species level of members in Cucurbitaceae family. The obtained information could be important for choosing proper DNA barcode loci for phylogenetic study of this crop family.